Decoding semiotic minimal genome: a non-genocentric approach - Gómez-Márquez, Carolina; Morales, J. Alejandro; Romero-Gutiérrez, Teresa; Paredes, Omar; Borrayo, Ernesto (Frontiers in Microbiology, 2024)
The search for the minimum information required for an organism to sustain a cellular-systemnetwork has rendered both the identification of a fixed number of known genes and those genes whose function remains to be identified. The approaches used in such search generally focus their analysis on coding genomic regions, based on the genome to proteic-product perspective.Such approaches leave other fundamental processes aside, mainly those that include higher-level information management. To cope with this limitation, a non-genocentric approach based on genomic sequence analysis using language processing tools and gene ontology, may prove an effective strategy for the identification of those fundamental genomic elements for life autonomy.Additionally, this approach will provide us with an integrative analysis of the information value present in all genomic elements, regardless of their coding status.